Investigating young water fractions in a small Mediterranean mountain catchment: Both precipitation forcing and sampling frequency matter. Issue 17 (23rd June 2020) - Gallart, Francesc; Valiente, María; Llorens, Pilar; Cayuela, Carles; Sprenger, Matthias; Latron, Jérôme
Abstract: The proportion of water younger than 2–3 months (young water fraction, F yw ) has become increasingly investigated in catchment hydrology. F yw is typically estimated by comparing seasonal tracer cycles in precipitation and streamflow, through water sampling. However, some open research questions remain, such as: (i) whether part of the summer precipitation should be discarded because the high evapotranspiration demand, (ii) how well F yw serves as a metric to compare catchments, and (iii) how sampling frequency affects F yw estimates. To address these questions, we investigated F yw in soil‐, ground‐ and stream waters for the small Mediterranean Can Vila catchment. Rainfall was sampled at 5‐mm intervals. Mobile soil water and groundwater were sampled fortnightly. Stream water was sampled depending on flow at variable time intervals (30 min to 1 week). Over 58 months, this sampling provided 1, 529 δ 18 O determinations. Isotopic analyses results led us to include summer precipitation in the input signal. We found the highest F yw in mobile soil waters (34%), while this was almost zero for groundwater except during wet periods. For stream waters, F yw depended on the discharge variations, so that the flow‐weighted young water fraction ( F yw * ) was 22.6%, whereas the time‐weighted F yw was just 6.2%. Both F yw * and its discharge sensitivity ( S d ) varied when different 12‐month sampling periods were investigated. The young water fraction that would be obtained from a virtual thorough sampling ( F yw * * ) was estimated from the S d and the observed stream flow. This showed an underestimation of F yw * * by 25% for the frequent dynamic sampling and 66% for weekly sampling, due to missing high flows. Our results confirm that F yw and its discharge sensitivity are metrics very sensitive to meteorological forcing during the analysed period. Thus, comparisons between catchments need long‐term mean annual values and their variability. Our findings also support the dependence of F yw estimates on the sampling rate and show the advantages of flow‐weighted analysis. Finally, catchment water turnover investigations should be accompanied by the analysis of flow duration curves. Abstract : High‐frequency discharge‐dependent stream water isotope sampling of highly responsive runoff in a Mediterranean headwater research catchment showed that any discrete sampling rate will underestimate young water fractions associated to the highest discharges; this loss may be assessed by using detailed flow records (figure). Our findings show that catchment's young water fraction and its discharge sensitivity metrics highly depend on the dynamic precipitation forcing, which is why young water fractions should be characterized using annual means and variances.